2002
DOI: 10.1017/s0033291702006712
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of symptom onset in first-episode schizophrenia

Abstract: True seasonal patterns are present in schizophrenia incidence, but their consistency with other published studies and wider significance, is difficult to ascertain because of different methods used in dating incidence of disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 19 publications
0
20
1
1
Order By: Relevance
“…Although the factors driving seasonal cortisol change need further clarification, it has been known for some time that seasonal trends occur in some diseases influenced by glucocorticoid levels. Increased incidence of cardiovascular and psychiatric disorders is reported in winter and a seasonal variation of autoimmune disorders is documented. A recent study by Dopico et al found a profound pro‐inflammatory transcriptomic profile during European winter with seasonal expression profiles of over 4000 mRNAs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the factors driving seasonal cortisol change need further clarification, it has been known for some time that seasonal trends occur in some diseases influenced by glucocorticoid levels. Increased incidence of cardiovascular and psychiatric disorders is reported in winter and a seasonal variation of autoimmune disorders is documented. A recent study by Dopico et al found a profound pro‐inflammatory transcriptomic profile during European winter with seasonal expression profiles of over 4000 mRNAs .…”
Section: Discussionmentioning
confidence: 99%
“…A model predicting circadian rhythms of cortisol with higher oscillations in winter, resulting in an exacerbated immune response and pro‐inflammatory state during winter months has also been suggested . It has been reported that cardiovascular, psychiatric and autoimmune disease have seasonal variation, conditions which are all influenced by glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%
“…Circadian rhythms modulate phenomena as diverse as bioluminescence in dinoflagellates1 and cognitive function in humans23, while circannual rhythms are seen in functions as diverse as flowering in plants4 and hibernation in chipmunks5, These rhythms also feature prominently in several human brain disorders. For example, prominent changes in circadian rest-activity6 and body temperature rhythms7 are seen in Alzheimer's disease, and there are seasonal rhythms of mood in seasonal affective disorder8, of symptom onset in schizophrenia9 and of human functional magnetic resonance imaging brain responses with cognitive tasks10.…”
mentioning
confidence: 99%
“…For example, Aviv et al (2011) 54 , as well as Amr and Volpe (2012) 56 did not find any seasonal effect on admission rates. In the Southern Hemisphere, Davies et al (2000) 57 found a peak in first episode schizophrenia admission in the winter (August), similar to Owens and McGorry (2003) 58 . In contrast, Daniels et al (2000) 59 did not find a seasonal association in Tasmania with admission with diagnoses of schizophrenia and bipolar disorder.…”
Section: Discussionmentioning
confidence: 66%